2019
DOI: 10.3389/fmicb.2019.01194
|View full text |Cite
|
Sign up to set email alerts
|

A Predominance of Clade 17 Candida albicans Isolated From Hemocultures in a Tertiary Care Hospital in Thailand

Abstract: Candida albicans is one of the most common human fungal pathogens. Candidemia has significant mortality globally. No epidemiological study of C . albicans based on multilocus sequence typing (MLST) has been conducted in Thailand. Therefore, MLST was used to study the molecular epidemiology of C . albicans blood strains in a large Thai teaching hospital. In vitro virulence phenotypes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Yeast carbon base and BSA were sterilized by 0.22 µL filter. The presence of the opaque halo of degradation around the colonies indicate positive protease activity [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast carbon base and BSA were sterilized by 0.22 µL filter. The presence of the opaque halo of degradation around the colonies indicate positive protease activity [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sheep blood was added when the autoclaved reagents were cooling to 50 °C. The presence of the translucent zone around colonies indicate the positive hemolytic activity [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Research has also found that the incidences of azoleresistant strains of C. tropicalis have increased, 30 and that the azole resistance of C. tropicalis is approximately ten times that of C. albicans (20.8% vs. 2.3%). 31,32 Hence, conducting a sensitivity test may play a pivotal role in determining the appropriate treatment for patients.…”
Section: Methodsmentioning
confidence: 99%
“…Relationship among concatenated sequences of the seven loci of each isolate were determined using unweighted pair group method with arithmetic averages (UPGMA) algorithm with p-distance model in Mega 6 software. A bootstrap of 1000 replications was used for the construction [ 9 , 19 ]. MLST clonal complexes (CC) and their founders were predicted by goeBURST algorithm ( http://www.phyloviz.net/goeburst/ ) to analyse population structure and evolutionary relationships between isolates.…”
Section: Methodsmentioning
confidence: 99%